2008
DOI: 10.1002/pits.20339
|View full text |Cite
|
Sign up to set email alerts
|

Preservice training in response to intervention: Learning by doing an interdisciplinary field experience

Abstract: Marking major changes in professional role performance, response to intervention (RTI) is now in the Individuals with Disabilities Education Act (IDEA, 2004) as a possible method to improve the identification of specific learning disabilities. Moreover, RTI and related concepts and initiatives have fundamentally influenced more general methods of prevention, instruction and intervention services, and decision making in schools. Although RTI will continue to evolve, core characteristics of RTI that form the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The majority of students reported little to no experience in visual analysis of single-case data. The undergraduate sample primarily was selected for convenience as part of a preliminary investigation of the impact of MASAJ; however, the undergraduates' level of training and experience in SCD (i.e., very little if any) is comparable to many school professionals, particularly in early phases of RTI implementation (Hawkins, Kroeger, Musti-Rao, Barnett, & Ward, 2008).…”
Section: Participantsmentioning
confidence: 99%
“…The majority of students reported little to no experience in visual analysis of single-case data. The undergraduate sample primarily was selected for convenience as part of a preliminary investigation of the impact of MASAJ; however, the undergraduates' level of training and experience in SCD (i.e., very little if any) is comparable to many school professionals, particularly in early phases of RTI implementation (Hawkins, Kroeger, Musti-Rao, Barnett, & Ward, 2008).…”
Section: Participantsmentioning
confidence: 99%
“…As an example of how training programs can better implement RTI in graduate training, Hawkins, Kroeger, Musti-Rao, Barnett, and Ward (2008) described the success of an interdisciplinary field experience in RTI for students studying school psychology and special education. Hawkins et al reported that opportunities for data-based decision making, evidence-based intervention, teaming, and problem solving were skills needed immediately by future professionals.…”
Section: Implications For Training Programs and Continuing Professionmentioning
confidence: 99%
“…As noted by Robichaux and Guarino (2012), an important facet of teacher preparation programs is an understanding of preservice teachers' levels of concern regarding the implementation of an innovation. To address the possibility that the problem results from a lack of RTI experience in clinical settings (i.e., schools) rather than a lack of practice in college classes, advanced practicums, and student teaching should include explicit experiences through partnerships with local school districts (Hawkins, Kroeger, Musti-Rao, Barnett, & Ward, 2008;Little et al, 2014). Explicit and direct instruction of the RTI process and its components, as an early intervention model, must be included in each course in a teacher preparation curriculum.…”
Section: Conclusion and Implications For The Fieldmentioning
confidence: 99%
“…It is critical that pre-service teachers' foundational skills be aligned with current innovations. As explained by Hawkins et al (2008), field experiences related to RTI in local schools should focus on the assistance of the design and evaluation of targeted interventions at each tier in an interdisciplinary, teambased manner. It is recommended that teacher educators increase preservice teachers' practical experiences for each component of RTI (Cavendish & Espinoza, 2013), as well as experiences with the process and implementation of this innovation (McCombes-Tolis & Spear-Swerling, 2010).…”
Section: Conclusion and Implications For The Fieldmentioning
confidence: 99%